Materials - Twist, Clint (New York : Bearport Pub., 2006)
Presents a children's book for early readers that describes different kinds of materials such as wood, metal, stone, paper, glass, plastic, and cloth.
Includes index.
Library Media Connection starred.
3.3
K-3
Keywords: Materials -- Juvenile literature; Materials; Materials